2021
DOI: 10.51507/j.jams.2021.14.4.127
|View full text |Cite
|
Sign up to set email alerts
|

Application of Auriculotherapy for Post-Burn Scar Syndrome in Young Adults with Major Burns

Abstract: Background: A burn scar is a type of hypertrophic scar that can cause significant clinical symptoms, discomfort, and post-burn scar (PBS) syndrome in up to 77% of patients with burn injuries. Medication and rehabilitation are rarely effective at managing patient discomfort, and both laser and surgical interventions are postponed until the scar stabilizes and discomfort is tolerable. Objectives: The present study was conducted to investigate the effectiveness of auricular acupuncture among burn victims from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Meanwhile, disturbed sleep could reduce the pain tolerance in patients [ 80 ]. Studies have shown that medicine intervention of pain and pruritus could promote sleep initiation, and improve sleep quality [ 15 , 81 , 82 ]. Our previous study also showed that the scar patients’ sleep quality was correlated with pain and pruritus, and fractional laser treatment can alleviate their pain and pruritus and realize sleep improvement [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, disturbed sleep could reduce the pain tolerance in patients [ 80 ]. Studies have shown that medicine intervention of pain and pruritus could promote sleep initiation, and improve sleep quality [ 15 , 81 , 82 ]. Our previous study also showed that the scar patients’ sleep quality was correlated with pain and pruritus, and fractional laser treatment can alleviate their pain and pruritus and realize sleep improvement [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The participants included in this study are the same as those in our previous study [17]. All participants were survivors of the Formosa Color Dust Explosion in Taiwan [11].…”
Section: Patient Selectionmentioning
confidence: 99%
“…The treatment tool was largely as described previously [17]. Briefly, the whole duration of the study was 29 days, and the intervals were a one-week intervention and a one-week break for two courses.…”
Section: Treatment Protocolmentioning
confidence: 99%
See 1 more Smart Citation